A study of 87 mycetoma patients seen at three health facilities in Nouakchott, Mauritania. (13th February 2021) - Kébé, M; Ba, O; Mohamed Abderahmane, M A; Mohamed Baba, N D; Ball, M; Fahal, A
Abstract: Background: Mycetoma is a chronic, progressive and destructive inflammatory disease that affects the skin, subcutaneous and other tissues. The objective of this study was to identify all cases of mycetoma diagnosed in three health facilities in Nouakchott, Mauritania during 2016–2018. Methods: This retrospective hospital-based study was conducted at the Dermatology, Orthopedics, Mycology and Pathology departments of the National Hospital Center of Nouakchott, the Military Hospital of Nouakchott and the National Institute for Research in Public Health of Nouakchott. Results: Eighty-seven patients were included in this study. They comprised 65 male patients (74.71%) and 22 females (25.28%) with a gender ratio of 4:1. The mean age was 41.87 y and ages ranged from 14 to 70 y. The most common age group was 40–45 y (11%). The foot was the most frequently affected site seen in 60 patients (69%), followed by ankle and hand with 6 patients each (7%). In the study, 56 patients (64%) had regional lymphadenopathy. Forty-nine patients (56%) had bone involvement. Thirty-two patients (37%) had medical treatment. Twenty-seven patients (87%) received fluconazole and four patients (13%) had co-trimoxazole treatment. Conclusion: The mycetoma patients seen in these three centres were mainly male farmers from rural areas. The lesions were seen mainly in the lower limbs and the majority had bone involvement radiologically.